Improvement of mechanized technology of potato growing at the private sites - Ляшенко, С. В. (Scientific Progress & Innovations, 2018)
The article provides justification and a new solution of the scientific and practical task, which takes place in the improvement of the mechanized technology of growing potatoes on the personal plots of ways of developing a mechanized operation with the use of means of minor mechanization of the traction class 0.1. The mechanized technology of growing potatoes under conditions of peasant farming is considered. The analysis and systematization of brands (models) of small-scale mechanization means for performing the corresponding operations of the technological process of growing potatoes is carried out. Defects of existing structures are determined and a new constructive solution is offered. The expediency of using the lem-and-lance hiller as a working organ that combines two mechanized operations of the technological process-weeding and humming is justified. It makes it possible to reduce the number of technological passes of the unit, to reduce labor productivity, to save fuel consumption, which in turn will increase the yield by 18 %. The analysis of constructions of the hinged equipment of means of small mechanization is given. The following effective parameters of the unit operation are recommended: the speed of movement is in the range of 0.091–0.637 m/s, the processing depth is 0.01–0.06 m. Under these conditions, the traction resistance will be 120–400 N. It has been established that to reduce labor costs in the technology of inter-row cultivation of plantations of potatoes and for the purpose of increasing the yield, it is necessary to use a lem-and-lancet hiller as a hinged equipment. It is recommended to use a lemically-stellate hiller for rural regions in the mechanized technology of growing potatoes.